THE INFLUENCE OF THE JOB COPYRIGHT LAW ON THE WELFARE AND RIGHTS OF WORKERS IN INDONESIA: Regulations, Job Creation Law, workers' rights - Ari Endrawati, Eka (Mendapo: Journal of Administrative Law, 2024)
The emergence of the Job Creation Law emerged as a government effort to increase economic efficiency and industrial competitiveness. This scientific article aims to critically analyze and evaluate the real influence of the implementation of the Job Creation Law on working conditions, welfare and protection of workers' rights in Indonesia. It is hoped that this scientific article will be able to carry out an in-depth evaluation of the impact of the Job Creation Law on the welfare and fulfillment of workers' rights in Indonesia in the context of changing labor laws. The approach used is descriptive qualitative, by collecting data through document studies and comparative analysis of similar cases in other countries, to assess the impact of the Job Creation Law on the welfare and rights of workers in Indonesia. The results of the analysis show that the Job Creation Law brings significant changes in labor regulations, but its impact on workers' welfare and rights tends to vary, with some aspects increasing efficiency and flexibility, while other aspects raise concerns about worker protection and work standards. The main conclusion from this research is that the Job Creation Law has had a complex impact on the employment environment in Indonesia, where there has been increased efficiency and flexibility for employers, but has also raised challenges and the need for increased protection for workers' rights. Therefore, further policy adjustments and developments are needed to ensure a balance between economic growth and worker welfare, as well as the fulfillment of fair and sustainable work standards. effective in making decisions.